1993
DOI: 10.1002/pd.1970130409
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a second gamete fusion after the first cleavage of the zygote in a 47,XX, + 18/70,XXX, + 18 mosaic. A remarkable diploid‐triploid discrepancy after CVS

Abstract: A 70,XXX,+18 karyotype was found by chorionic villus sampling, while the fetal fibroblast culture of the affected fetus revealed a 47,XX,+18 karyotype. From several possible mechanisms, we assume that a second gamete fusion occurred after the first cell division of the zygote. According to this interpretation, the mosaicism arose in very early pregnancy (at the two-cell stage). This discrepancy can therefore be explained by selection pressure, due to the differentiation processes in the embryonic tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Tuerlings et al [1993] reported a 70,XXX,þ18 karyotype in chorionic villus sampling, while fetal fibroblasts showed a 47,XX,þ18 karyotype. These findings suggest delayed inclusion of a second gamete after the establishment of a trisomy 18 zygote.…”
Section: Discussionmentioning
confidence: 96%
“…Tuerlings et al [1993] reported a 70,XXX,þ18 karyotype in chorionic villus sampling, while fetal fibroblasts showed a 47,XX,þ18 karyotype. These findings suggest delayed inclusion of a second gamete after the establishment of a trisomy 18 zygote.…”
Section: Discussionmentioning
confidence: 96%
“…The concurrent ®nding of diploid and triploid cell lines can be explained by a vanishing twin and chimerism (Tuerlings et al, 1993), incorporation of a second male gamete (Tuerlings et al, 1993), or the second polar body (Kennerknecht et al, 1993;Muller et al, 1993) at an early cell division stage. As discussed by Tuerlings et al (1993), a vanishing twin and chimerism probably play a minor role in the production of diploid/triploid mosaics since sex discrepancies are only rarely observed.…”
Section: Discussionmentioning
confidence: 99%
“…Post and Nijhuis (1992) reported a 46,XX/47,XX,+16 karyotype in a CVB long-term culture (direct preparations failed), but the fetus had a 69,XXX karyotype. Tuerlings et al (1993) found a 70,XXX,+18 karyotype in CVB directs, but the fetus had a 47,XX,+18 karyotype. Retrospective analysis of the CVB cultures showed both cell lines.…”
Section: Introductionmentioning
confidence: 89%
“…Human CPM usually involves mosaicism for a trisomic (Ts) cell line, but not all trisomies are equally associated with CPM (Wolstenholme 1996) and CPM involving polyploid mosaicism also occurs (Tuerlings et al . 1993, Kalousek 1994, Wolstenholme et al .…”
Section: Introductionmentioning
confidence: 99%
“…Some human triploid/diploid mosaics show CPM (Sarno et al . 1993, Tuerlings et al . 1993, Daniel et al .…”
Section: Introductionmentioning
confidence: 99%